A double-blind randomized controlled trial of mifepristone or placebo before buccal misoprostol for abortion at 14–21 weeks of pregnancy. Issue 1 (July 2015) - Dabash, Rasha; Chelli, Héla; Hajri, Selma; Shochet, Tara; Raghavan, Sheila; Winikoff, Beverly
Abstract: Objective: To assess differences in outcomes of misoprostol with or without mifepristone for second-trimester abortion. Methods: A randomized, double-blind, placebo-controlled trial of buccal misoprostol following placebo or 200 mg mifepristone was done in Tunisia among women presenting for abortions at 14–21 weeks of pregnancy between August 2009 and December 2011. Women with a live fetus, a closed cervical os, no cervical bleeding, and no contraindications to study drugs were eligible and underwent randomization (block size 10). Participants returned 24 hours later to receive 400 μg buccal misoprostol every 3 hours until complete fetal and placental expulsion (maximum 10 doses, five per 24-hour period). The primary outcomes were rates of complete uterine evacuation at 48 hours and time to expulsion. Results: A total of 120 women were evenly randomized to treatment. Complete uterine evacuation at 48 hours was recorded in 55 (91.7%) women in the combined group versus 43 (71.7%) in the misoprostol alone group (relative risk 1.28; 95% confidence interval 1.07–1.53). Mean time to complete abortion was 10.4 ± 6.6 hours in the group who received mifepristone versus 20.6 ± 9.7 hours in the misoprostol alone group ( P  < 0.001). Side effects were similar in both groups. Conclusion: Adding mifepristone before misoprostol can improve the quality of second-trimester abortion care by making the process faster. ClinicalTrials.gov: NCT00969982.